Membrane Fluidity Is Related to the Extent of Glycation of Proteins, but not to Alterations in the Cholesterol to Phospholipid Molar Ratio in Isolated Platelet Membranes from Diabetic and Control Subjects - Winocour, Peter D; Watala, Cezary; Kinglough-Rathbone, Raelene L (Thrombosis and Haemostasis, 1992)
Platelets from diabetic subjects are hypersensitive to aggregating agents in vitro. Membrane fluidity modulates cell function and we previously reported reduced membrane fluidity associated with hypersensitivity to thrombin in intact platelets from diabetic subjects. Reduced membrane fluidity and hypersensitivity to agonists has also been reported in platelets from non-diabetic subjects whose platelets have an increased cholesterol/phos-pholipid molar ratio. Glycation of platelet membrane proteins is enhanced in diabetic subjects, and could contribute to the decreased membrane fluidity in these platelets. We examined the relation among fluidity, cholesterol/phospholipid molar ratio, and glycation of proteins in isolated platelet membranes from diabetic and control subjects. Seven poorly controlled diabetic subjects were compared with 7 age- and sex-matched control subjects. The mean steady-state fluorescence polarization value in 1,6-diphenyl-1,3,5-hexatriene-labeled isolated platelet membranes from diabetic subjects (0.184 ± 0.004) was significantly greater than from control subjects (0.171 ± 0.004, p <0.01); thus, fluidity in platelet membranes from diabetic subjects is decreased. Reduced fluidity in platelet membranes from diabetic subjects could not be attributed to changes in the cholesterol/phospholipid molar ratio. Total or very low density (VLDL), low density (LDL), or high density (HDL3) lipoprotein cholesterol concentration in plasma was not significantly different between groups, but the ratio of VLDL + LDL to HDL2 + HDL3 cholesterol was significantly greater in diabetic subjects (4.79 ± 0.73) than in control subjects (2.54 ± 0.30, p <0.02). Proteins were glycated significantly more extensively in platelet membranes from diabetic subjects (25.5 ± 0.9 nmol glucose/mg protein) than those from control subjects (21.0 ± 0.6 nmol glucose/mg protein, p <0.001). The extent of glycation of proteins in platelet membranes correlated significantly with the steady state fluorescence polarization values for platelet membranes from diabetic and control subjects (r = 0.715, p <0.01). More extensive glycation of proteins appears to be associated with reduced fluidity of platelet membranes from diabetic subjects, but not with increased cholesterol/phospholipid molar ratio.